Menyelami Lebih Dalam Keberhasilan Badan Usaha Milik Desa Bersama (BUMDes) di Indonesia: Sebuah Pendekatan Interpretive Structural Modeling (ISM) - Sari, Agni; Ilham, Teguh (Jurnal Bina Praja, 2024)
The establishment of Joint Village-Owned Enterprises (Joint-BUMDes) presents an opportunity to create a collaborative network among villages, addressing the challenge of hindered business growth commonly faced by single-village enterprises. Therefore, this research aims to explore and analyze key enablers of Joint-BUMDes development using an interpretive structural modeling (ISM) approach and provide strategic recommendations for their growth. Based on literature review and semi-structured interviews with 8 informants, nine enablers were identified. These served as the basis for constructing a questionnaire distributed to three respondents who were purposely selected to establish contextual relationships. The ISM analysis prioritized interventions based on enablers located in Quadrant III and IV from the MICMAC analysis and the highest levels in the ISM interaction model. Key enablers include the village chief's political influence, managerial and technical skills, and leadership characteristics, as well as government support, equality in capabilities among villages, and the founding initiative. The conclusion drawn is that political and management factors predict the success of Joint-BUMDes and influence other factors. Therefore, addressing these enablers is crucial for the successful development of Joint-BUMDes in Indonesia. Apart from these practical implications, this study enriches the literature on social enterprises in Indonesia, which has thus far been limited to single village BUMDes and fragmented in analyzing influencing factors.